The role of crustal fluids in tectonics of north-central Turkey inferred from three-dimensional magnetotellurics - Özaydın, Sinan. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2011., 2017)
Central Pontides have been an active margin to Laurasia since the Paleozoic times. They consists of geological footprints of several episodes of subduction-accretion events and collisional tectonics. For these reasons, they have been a great laboratory for examining the evolution of Anatolia and the Tethyan oceans for decades. Many geological studies have been made with di erent methodologies, however there is still a lack of geophysical results in the region. In search of this potential, 26 wide-band (320 - 0.00055 Hz) magnetotelluric measurements were deployed to depict the geo-electric properties in a crustal range. The data were collected to form a 190-km-long pro le, passing through C ank r Basin, _Izmir-Ankara-Erzincan Suture Zone (_IAES), Tosya Basin, North Anatolian Fault Zone, Central Pontides Super-complex, Kure Complex and the Pontide Arc. Phase tensor analyses and 3-D inversions were applied to this data to develop a model that accurately display the geo-electrical characteristics of the region. Phase tensor analyses point out that the regional geo-electric strike angles t within the N80 E {u100000} N90 E range with the exception of N75 E for the data near C ank r Basin and K z l rmak Fault. Lack of oblique conductors in the data reduces the dimensional complexity and helps the 3-D inversion schemes to be more accurate for a pro le based measurement. Two distinct 3-D models were developed: (1) A model that covers whole frequency range and stations, (2) another model that aims to picture the area in the vicinity of North Anatolian Fault (NAF). For the second model, data from only ten stations (stations from 9 to 19) were used down to a frequency of 0.035 The nal models attained from the 3-D inversions were compatible with the rheological environment around the NAF that lacks moderate seismicity and ensures a deeper brittle to ductile transition by two resistive features appearing on both sides of the fault. This characteristic is present at the southern side of the fault via obducted ophiolites and intra-oceanic arc units, while the other side is made up of metamorphic rocks of Central Pontide Supercomplex. Both of the bodies are geological units, which are devoid of e ective porosity that can enhance mechanical strength along the fault and inhibit uid ow towards the fault zone. The NAF model demonstrate that the Tosya Basin appears as a conductive syncline where its basement is placed between 3.6 and 4.3 km. Fault zone conductors were found within this model matches well with the spatial positions of the NAF and related subsidiary faults. South of the suture zone, a buried thrust belt is visible with several norwarddipping conductive-resistive interfaces. C ank r Basin appears as a conductive zone with several resistive interruptions. Projected earthquakes correlate well with the resistivity variations indicating fault-like structures. Beneath the northernmost features in the model, the resistive characteristics appear in deeper structure con rming the crustal thickening in the region. North of the fault, CPS shows itself as a downward convex shaped resistive body that demonstrates heterogeneous conductive features near the surface. C angalda g Complex, placed at the tip of the CPS, exhibits highly resistive values beneath the Kastamonu Basin. A large conductive anomaly, which appears to have an upwelling feature was found beneath this region. Although the source of this uid-rich zone is not resolved or clear, existence of this conductive region might have important implications on the seismic nature, rheological attributes and geological evolution of the area.
Keywords: Geology, Structural -- Turkey.